2001
DOI: 10.1016/s0006-3495(01)76159-0
|View full text |Cite
|
Sign up to set email alerts
|

Coiled-Coil Unwinding at the Smooth Muscle Myosin Head-Rod Junction Is Required for Optimal Mechanical Performance

Abstract: Myosin II has two heads that are joined together by an alpha-helical coiled-coil rod, which can separate in the region adjacent to the head-rod junction (Trybus, K. M. 1994. J. Biol. Chem. 269:20819-20822). To test whether this flexibility at the head-rod junction is important for the mechanical performance of myosin, we used the optical trap to measure the unitary displacements of heavy meromyosin constructs in which a stable coiled-coil sequence derived from the leucine zipper was introduced into the myosin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 24 publications
(31 reference statements)
2
16
0
1
Order By: Relevance
“…The observation of different structures of the N terminus of S2, ranging from disordered in scallop S2N51 (9) to partially ordered͞␣-helical (WT-S2-⌬) to coiled coil (E924K-S2-⌬), indi- cates that only a small energy barrier needs to be overcome to induce different structural states in the first dozen residues. This small barrier may help in reconciling previous studies that demonstrated the necessity for the presence of the labile native S2 sequence in generating a full powerstroke (14) but found uncoiling limited to only a small part of S2 in two-headed rigor binding to actin (3,15).…”
Section: Resultssupporting
confidence: 74%
“…The observation of different structures of the N terminus of S2, ranging from disordered in scallop S2N51 (9) to partially ordered͞␣-helical (WT-S2-⌬) to coiled coil (E924K-S2-⌬), indi- cates that only a small energy barrier needs to be overcome to induce different structural states in the first dozen residues. This small barrier may help in reconciling previous studies that demonstrated the necessity for the presence of the labile native S2 sequence in generating a full powerstroke (14) but found uncoiling limited to only a small part of S2 in two-headed rigor binding to actin (3,15).…”
Section: Resultssupporting
confidence: 74%
“…We were unable to find any satisfactory models with such a coiled rod conformation. Our model is consistent with the idea that optimal mechanical performance of SMM may require the rod to uncoil near the heads (39).…”
supporting
confidence: 87%
“…34). Another explanation is that muscle myosin needs both heads to generate maximum force and motion (32) and that coordination of the heads requires the region of the coiled-coil rod near the S2-segment to unwind or breathe (12). It is possible that the L908V and the D906G mutations exert their effect through alterations to head-head interactions by virtue of their effect on S2-segment flexibility.…”
Section: Discussionmentioning
confidence: 99%